2011
DOI: 10.1021/jp203664r
|View full text |Cite
|
Sign up to set email alerts
|

A Study To Control Chemical Reactions Using Si:2p Core Ionization: Site-Specific Fragmentation

Abstract: In an aim to create a "sharp" molecular knife, we have studied site-specific fragmentation caused by Si:2p core photoionization of bridged trihalosilyltrimethylsilyl molecules in the vapor phase. Highly site-specific bond dissociation has been found to occur around the core-ionized Si site in some of the molecules studied. The site specificity in fragmentation and the 2p binding energy difference between the two Si sites depend in similar ways on the intersite bridge and the electronegativities of the included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
48
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 36 publications
0
48
0
Order By: Relevance
“…17 carried out a study on ozone, and Nagaoka et al [18][19][20] investigated the dissociation of some trihalosilyltrimethylsilyl-compounds upon core ionisation of the silicon 1s and 2p inner shells. Site-specific photochemistry arising from initial ionisation at the allimportant carbon atoms of organic molecules was studied by Itälä et al 21 for the case of pyrimidine and by some of us 22 for the case of ethyl trifluoroacetate.…”
Section: Introductionmentioning
confidence: 99%
“…17 carried out a study on ozone, and Nagaoka et al [18][19][20] investigated the dissociation of some trihalosilyltrimethylsilyl-compounds upon core ionisation of the silicon 1s and 2p inner shells. Site-specific photochemistry arising from initial ionisation at the allimportant carbon atoms of organic molecules was studied by Itälä et al 21 for the case of pyrimidine and by some of us 22 for the case of ethyl trifluoroacetate.…”
Section: Introductionmentioning
confidence: 99%
“…More generally, x-ray photoionization proceeds via electron promotion into the continuum and relaxation by Auger decay. Experimentally this process has been studied [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] with electron-ion coincidence methods. Site-selectivity is obtained by exciting or ionizing atoms of different elements [10][11][12]22 or, for atoms of same elements, by using site-specific chemical shifts in a variety of medium-sized carbon 9,17,18,20,24,25 and silicon-containing 13,16,19 molecules.…”
mentioning
confidence: 99%
“…The site-specific excitation has been proposed as a tool for selectively breaking particular bonds of a molecule. A number of studies have been performed on this topic using both resonant core excitation [5][6][7][8][9][10][11][12][13][14][15][16][17] and core ionization [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], showing varying degree of selectivity. A recent study [31] on core ionization of molecules has shown only a small degree of selectivity which was explained by the delocalized character of the valence orbitals.…”
Section: Introductionmentioning
confidence: 99%